Reconciling neuronal representations of schema, abstract task structure, and categorization under cognitive maps in the entorhinal-hippocampal-frontal circuits. (December 2022) - Igarashi, Kei M.; Lee, Jason Y.; Jun, Heechul
Abstract: Learning leads to a neuronal representation of acquired knowledge. This idea of knowledge representation was traditionally developed as a "cognitive map" of spatial memory represented in the hippocampus. The framework of cognitive mapping has been extended in the past decade to include not only spatial memory, but also non-spatial factual and temporal memory. Following this conceptual advancement, a line of recent neurophysiological research discovered such knowledge representations not only in the hippocampus, but also in the entorhinal cortex and frontal cortex. Although the distinct terms "cognitive map, " "schema, " "abstract task structure" or "categorization" were used in these studies, it is likely that these terms can be reconciled as a common mechanism of learned knowledge representations. Future experimental work will be required to differentiate the parametric nature of knowledge representations across brain areas.